Molecular identification and enzymatic properties of laccase2 from the diamondback moth Plutella xylostella (Lepidoptera: Plutellidae) - Zhen-gang LIU; Huan-huan WANG; Chao-bin XUE (Journal of Integrative Agriculture)
Laccase (EC 1.10.3.2) is known to oxidize various aromatic and nonaromatic compounds via a radical-catalyzed reaction, which generally includes two types of laccase, Lac1 and Lac2. Lac1 oxidizes toxic compounds in the diet, and Lac2 is known to play an important role in melanizing the insect exoskeleton. In this study, we cloned and sequenced the cDNA of the diamondback moth, Plutella xylostella Lac2 (PxLac2), from the third instar larvae using polymerase chain reaction (PCR) and rapid amplification of cDNA ends techniques. The results showed that the full-length PxLac2 cDNA was 1 944 bp long and had an open reading frame of 1 794 bp. PxLac2 encoded a protein with 597 amino acids and had a molecular weight of 66.09 kDa. Moreover, we determined the expression levels of PxLac2 in different stages by quantitative PCR (qPCR). The results indicated that PxLac2 was expressed differently in different stages. We observed the highest expression level in pupae and the lowest expression level in fourth instar larvae. We also investigated the enzymatic properties of laccase, which had optimal activity at pH 3.0 and at 35°C. Under these optimal conditions, laccase had a Michaelis constant (Km) of 0.97 mmol L−1, maximal reaction speed (Vm) of 56.82 U mL−1, and activation energy (Ea) of 17.36 kJ mol−1 to oxidize 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid ammonium salt). Type II copper enhanced laccase activity below 0.8 mmol L−1 and reduced enzyme activity above 0.8 mmol L−1 with an IC50 concentration of 1.26 mmol L−1. This study provides insights into the biological function of laccase.